Effect of pH, acid and thermal treatment conditions on Co/CNT catalyst performance in fischer-tropsch reaction - Akbarzadeh, O. (2019)
Multiwalled carbon nanotubes (CNT) supported cobalt oxide was prepared as a catalyst by strong electrostatic adsorption (SEA) method. The CNT support was initially acid- and thermal-treated in order to functionalize the support to uptake more Co clusters. The Co/CNT were characterized by a range of analytical methods including transmission electron microscopy (TEM), temperature programmed reduction with hydrogen (H2-TPR), X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), Raman spectroscopy, atomic absorption spectroscopy (AAS), Zeta sizer particle size analysis and Brunauer-Emmett-Teller (BET) surface area analysis. TEM images showed cobalt particles were highly dispersed and impregnated at both exterior and interior walls of the CNT support with a narrow particle size distribution of 6-8 nm. In addition, the performance of the synthesized Co/CNT catalyst was tested using Fischer-Tropsch synthesis (FTS) reaction which was carried out in a fixed-bed micro-reactor. H2-TPR profiles indicated the lower reduction temperature of 420 °C was required for the FTS reaction. The study revealed that cobalt is an effective metal for Co/CNT catalysts at pH 14 and at 900 °C calcination temperature. Furthermore, FTS reaction results showed that CO conversion and C5+ selectivity were recorded at 58.7 and 83.2 respectively, which were higher than those obtained using a Co/CNT catalyst which pre-treated at a lower thermal treatment temperature and pH. © 2019 by the authors.